Analysis of Relationship Structure between Creativity and Character of Young Children - Seo, Hyunjung; Kim, Kyungchul; Cho, Bookyung (International Journal of Engineering and Technology, 2019)
This study aims to provide basic data on the relationship between creativity and character education by examining the relationship structure between the sub-variables of creativity and character.Â For this, the creativity and character of 189 5-year-old children (98 boys, 90 girls) from eight classes in Chungcheongbuk-do, Korea were measured using the Creativity Measurement Scale and Character Measurement Scale for Teachers, and canonical correlation analysis was performed on the sub-variables of creativity and character.Â Prior to canonical correlation analysis, the assumption of normality and assumption of appropriateness of relationships were reviewed.Â As a result of this study, creativity and character showed a correlation, implying that the creativity and character development influence each other.Â Also, immersion in creativity and the basic life habits of character showed a strong influence in canonical correlation.Â This shows that immersion has a significant influence on character development, such as basic life habits, and a thorough observation and thinking process in problem situations is needed prior to habituation in terms of character education as well. The results of this study imply that creativity and character development may be complementary, and education that can develop both at the same time is necessary. Creativity-character education is a good start to develop these abilities.Â Â